Molecular Characterization, Biochemical Isolation and Identification of Salmonella species from Poultry Liver and Fecal Samples at Dinajpur, Bangladesh - Husneid, Md; Ahmed, A.S.; Hussain, M.S.; Mahatab, T. (Nepalese Journal of Agricultural Sciences, 2026)
Poultry products are the main means of transmission for Salmonellosis, a significant foodborne infection in the world. The purpose of this work was to separate, biochemically identify, and molecularly describe Salmonellosis from samples of poultry feces and liver. A total of 150 samples (50 livers, 100 cloacal swabs) were collected from Dinajpur broiler farms and transferred to the Department of Microbiology, HSTU, Dinajpur, in an ice box with PBS by maintaining aseptic conditions. The samples were streaked in Nutrient Agar 37°C following incubation for 24 hour and sub-cultured on selective media MacConkey Agar at 37°C for 24 hours. Then Salmonella was identified in Gm staining technique. Then Colonies were streaked to S.S Agar(Salmonella Shigella Agar) and finally biochemical tests like Motility Indole Urease (MIU), Simmons citrate, Indole, Methyl Red, and Triple Sugar Iron (TSI) utilization were positive. Then Serological test was performed, followed by PCR-based confirmation including genomic DNA isolation and gel electrophoresis. Isolates confirmed as Salmonella were serotyped and further characterized by Polymerase Chain Reaction (PCR) targeting the invA genus-specific gene. The overall prevalence of Salmonella was 13.3 %, with a higher isolation rate from fecal samples (14%) than liver samples (12%).More poultry fecal and liver samples will be studied in future to carry out research.